1997
DOI: 10.1002/(sici)1096-9861(19970203)378:1<135::aid-cne8>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of TrkB in the central nervous system of the adult rat

Abstract: The TrkB family of transmembrane proteins serve as receptors for brain-derived neurotrophic factor (BDNF), neurotrophin (NT)-4/5, and possibly NT-3, three members of the neurotrophin family of neurotrophic factors. In order to understand the potential roles played by these receptors, we have examined the distribution of the TrkB receptor proteins in the adult rat brain by using immunohistochemistry. Several different antisera, directed against either synthetic peptides corresponding to different regions of Trk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
175
0
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 397 publications
(190 citation statements)
references
References 115 publications
14
175
0
1
Order By: Relevance
“…A number of Trk trafficking events occur in neurons. In CNS neurons, the BDNF receptor TrkB has been shown to be present in dendritic spines, axon initial segments, axon terminals, dendritic shafts, and cell bodies (7)(8)(9). Except for dendritic spines, TrkB receptors in these cellular regions are often found in intracellular membranes, suggesting that extensive trafficking of this receptor occurs in neurons (8).…”
Section: Introductionmentioning
confidence: 99%
“…A number of Trk trafficking events occur in neurons. In CNS neurons, the BDNF receptor TrkB has been shown to be present in dendritic spines, axon initial segments, axon terminals, dendritic shafts, and cell bodies (7)(8)(9). Except for dendritic spines, TrkB receptors in these cellular regions are often found in intracellular membranes, suggesting that extensive trafficking of this receptor occurs in neurons (8).…”
Section: Introductionmentioning
confidence: 99%
“…BDNF mRNA levels are low in the embryonic brain, but increase rapidly during postnatal development [123]. Widespread expression of mRNAs for BDNF and its receptor trkB in the CNS suggests an important role for this neurotrophin [124,125]. BDNF affects the survival or differentiation of cholinergic neurons [42,126], dopaminergic and GABAergic neurons [127,128], retinal ganglion cells [129], cerebellar granule cells [130], striatal neurons [131], cortical neurons [41,132], and subpopulations of sensory neurons.…”
Section: Bdnfmentioning
confidence: 99%
“…TrkB is the preferred receptor for BDNF and is expressed on both neuronal and non-neuronal cells in many areas of the brain [124,142]. Although it has been demonstrated that trkB is able to transduce BDNF signal in the absence of p75NTR in cultured cells transfected with the trkB gene, BDNF normally binds to both receptors.…”
Section: Bdnfmentioning
confidence: 99%
“…This antibody has also been used for the detection of fl-Trk B in both the neurons of the rat CNS (Cellerino et al 1996;Ferrer et al 1997;Yan et al 1997a;Goutan et al 1998;Inoue et al 1998;Costantini et al 1999) and the monkey hippocampal formation . All these findings indicate that the antibody used in the present study specifically recognizes fl-Trk B.…”
Section: Specificity Of Antibodymentioning
confidence: 99%
“…Recent immunohistochemical (Muragaki et al 1995;Cellerino et al 1996;Fryer et al 1996;Yan et al 1997a) and in situ hybridization studies Masana et al 1996) have shown that fl-Trk B and its mRNA are highly expressed in the cortical neurons. In addition, BDNF (Dugich-Djordjevic et al 1995;Kawamoto et al 1996;Schmidt-Kastner et al 1996;Conner et al 1997;Yan et al 1997b) and BDNF mRNA (Ernfors et al 1990Hofer et al 1990;Friedman et al 1991;Huntley et al 1992;Schmidt-Kastner et al 1996;Conner et al 1997) have also been detected in the cortical neurons.…”
Section: Introductionmentioning
confidence: 99%